Central Hyperthermia Treated with Baclofen in a Patient with Epidural Hematoma - Bohara, Manoj; Bohara, Prasanna K; Chaudhary, Lalit; Pant, Basant (Nepal Journal of Neuroscience, 2016)
Central hyperthermia is characterized by a rapid-onset elevated temperature, marked temperature fluctuation, and poor response to antipyretics and antibiotics. It is caused by impairment of the central thermoregulatory pathways and is associated with high morbidity and mortality. We report on a case of 31-year old male who sustained fall injury with massive epidural hematoma and a high-grade fever of 40°C on presentation. Following cranio to my and evacuation of hematoma, antipyretics and antibiotics were used for high-grade fever but were not effective. Baclofen was orally administered which effectively controlled the fever. Here, we also discuss the possible central mechanisms for this effect of baclofen and show that baclofen may be an effective treatment in central hyperthermia. Nepal Journal of Neuroscience. Vol. 13, No. 2, 2016, Page: 102-104